Sudden Cardiac Death in Athletes: Magnitude, Causes, and Prevention Strategies - A Literature Review - Melnyk, Bohdan; Rygielski, Artur; Latour, Emilia; Latour, Marianna; Judek, Roksana; Melnyk, Mariia (Quality in Sport, 2024)
Sudden cardiac death (SCD) in athletes, though rare, is the leading cause of exercise-related mortality and poses significant concern due to the symbolic health and vitality of athletes. This review examines the epidemiology, causes, and prevention strategies of SCD in athletes. SCD, defined as sudden death presumed to be of cardiac origin within one hour of symptom onset, affects athletes variably depending on age, race, and type of sports. Key causes include hypertrophic cardiomyopathy (HCM) and arrhythmogenic right ventricular cardiomyopathy (ARVC) in younger athletes, and coronary artery disease (CAD) in older athletes. Ion channelopathies and structural heart diseases also contribute significantly. Preparticipation screening (PPE) involving ECGs, lifestyle adjustments, and medical interventions are critical in prevention. Continuous research and adaptive guidelines are essential for safeguarding athletes against these fatal events. Keywords: sudden cardiac death, athletes, sports, exercise, cardiovascular diseases, hypertrophic cardiomyopathy, arrhythmogenic right ventricular cardiomyopathy, coronary artery disease, ion channelopathies, long QT syndrome, Brugada syndrome, preparticipation screening, electrocardiogram (ECG), risk factors, prevention strategies.